Dampak Pendidikan dan Pelatihan Manajemen oleh Perpusnas terhadap Kinerja Pustakawan - Dedi Junaedi; Abdul Rahman Saleh; Khosy Alfin Maulana; Muhammad Ansyari Tantawi (Jurnal Pustakawan Indonesia, 2022)
Introduction. Indonesia has about 5 thousand librarians registered with the National Library. The condition of the librarian's competence varies greatly. The National Library of Indonesia has conducted training for competency improvement, but its success is not yet known. To determine the effectiveness of the training, this research was conducted. Research methods. This research is a survey research. The sample is a librarian who received management training from the National Library of Indonesia. The sample was drawn based on purposive sampling with a three-year limit of participants, namely 2017, 2018, and 2019. The questionnaire was made using a google survey. The incoming data is then tabulated, processed and analyzed. Results and Discussion. A total of 34 respondents (91.89%) think that management training is very useful. Twenty-nine respondents (78.38%) felt that 2 weeks was sufficient time for training. The training subject "Indonesian Library Development Policy" is considered the most helpful in the work. Meanwhile, the training subject "Management of library promotion and cultivating a love of reading" is a training subject that is considered very important for librarians. All respondents said that this education and training needs to be maintained. Conclusion. Respondents agree that management training is useful to support their work. The available training time is considered sufficient. The most useful training subject of the basic group is “Indonesian library development policy”. The managerial ability of the respondents became better after the training. Respondents agreed that this training should be maintained.